1960
DOI: 10.1063/1.1730711
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Binary Mixtures of Diatomic and Monatomic Gases

Abstract: Thermal conductivity of the binary mixtures of O2–He, O2–Ne, O2–Kr, and O2–Xe have been measured at 30°C and 45°C for various compositions by using the thick-wire-variant of the hot-wire method. For pure O2 the experimental value of the thermal conductivity is lower than that given by the recent theory of Hirschfelder based on the assumption of local chemical equilibrium, and consequently the values calculated from Hirschfelder's formula for the mixture conductivities are also expected to be higher than the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…In the above equations m 0 and k 0 are kinematic viscosity and thermal conductivity respectively of the atmospheric air at sea level, q the density, a the thermal diusivity, g the absolute viscosity and c p the speci®c heat of the gas or gas mixtures. The numerical values of k and m are given in Table 2 (Srivastava and Barna 1960;Wargaftik 1972). Rapp (1970) has also described the ratio between the evaporative heat transfer coecient (h e ) at the interface between the body and a gas underwater and the same parameter at sea level in atmospheric air:…”
Section: Theorymentioning
confidence: 99%
“…In the above equations m 0 and k 0 are kinematic viscosity and thermal conductivity respectively of the atmospheric air at sea level, q the density, a the thermal diusivity, g the absolute viscosity and c p the speci®c heat of the gas or gas mixtures. The numerical values of k and m are given in Table 2 (Srivastava and Barna 1960;Wargaftik 1972). Rapp (1970) has also described the ratio between the evaporative heat transfer coecient (h e ) at the interface between the body and a gas underwater and the same parameter at sea level in atmospheric air:…”
Section: Theorymentioning
confidence: 99%
“…Figure 7 shows comparisons of experimental thermal conductivity values [17] for helium-oxygen and xenon-oxygen mixtures at 30°C compared to theoretical values calculated using Equation (8). The maximum relative differences between the theory and experiment are 4.2% at X He = 0.68 and 4.7% at X Xe = 0.27, respectively.…”
Section: Discussionmentioning
confidence: 99%
“… Thermal conductivity at 30°C for He-O 2 and Xe-O 2 mixtures using Equation (8), based on a weighted average of the molar fractions and from experimental measurements [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…and 0" to 1200" C. H e showed that the simple mixing law using partial pressures was within 2% of the more complicated calculation of Buddenberg and Wilke. by (66, 105) three methods 20" and 4 5 O C. ; thick wire method (97) 30' and 4 5 O C.; Hirschfelder theory, (13) 30' and 45' C. Exptl., 270' C. ; calcd., 20O0-15OO0 K. (30) Exptl., 29 ' and 520' C.; also calcd.…”
Section: Generalmentioning
confidence: 99%